2011
DOI: 10.1016/j.bios.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel LTCC-potentiometric microfluidic device for biparametric analysis of organic compounds carrying plastic antibodies as ionophores: Application to sulfamethoxazole and trimethoprim

Abstract: A B S T R A C TMonitoring organic environmental contaminants is of crucial importance to ensure public health. This requires simple, portable and robust devices to carry out on-site analysis. For this purpose, a low-temperature co-fired ceramics (LTCC) microfluidic potentiometric device (LTCC/µPOT) was developed for the first time for an organic compound: sulfamethoxazole (SMX).Sensory materials relied on newly designed plastic antibodies. Sol-gel, self-assembling monolayer and molecular-imprinting techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Electrodes can be deposited onto LTCC using expansion matched metal pastes. In this manner Almeida et al 32 used an LTCC device with potentiometric detection to analyze sulfamethoxazole and trimethoprim in fish farm water. Electrophoretic separations have been demonstrated for phenolic compounds 33, 34 and inorganic ions.…”
Section: Materials For Microfluidicsmentioning
confidence: 99%
“…Electrodes can be deposited onto LTCC using expansion matched metal pastes. In this manner Almeida et al 32 used an LTCC device with potentiometric detection to analyze sulfamethoxazole and trimethoprim in fish farm water. Electrophoretic separations have been demonstrated for phenolic compounds 33, 34 and inorganic ions.…”
Section: Materials For Microfluidicsmentioning
confidence: 99%
“…At a first glance, this may seem a similar process to that presented by Almeida et al (2011). However, the chemical path follows a completely different scheme, accounting for the great chemical differences between the silica spheres employed there and the CN used here.…”
Section: Imprinting On Carbon Nanostructuresmentioning
confidence: 57%
“…All these are too expensive or unable to carry out on-site analysis. The potentiometric sensors described so far do not have the necessary LOD for field applications (Almeida et al, 2011(Almeida et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature co-fired ceramics (LTCC) were laminar in nature, thus helping in the construction of a three-dimensional device where a stacked or a layered structure could be build. In this manner, Almeida et al (2011) used an LTCC device with potentiometric detection to analyze sulfamethoxazole and trimethoprim in fish farm water. Fakunle and Fritsch (2010) demonstrated that LTCC devices provide low levels of non-specifically adsorbed molecules in immunoassays such as the enzyme-linked immunosorbent assay (ELISA).…”
Section: Traditional Packaging Techniquesmentioning
confidence: 99%